A Chinese randomized prospective trial of floppy Nissen and Toupet fundoplication for gastroesophageal disease. (November 2015) - Wang, Bin; Zhang, Wei; Liu, Sheng; Du, Zhipeng; Shan, Chengxiang; Qiu, Ming
Abstract: Introduction: To evaluate the clinical outcomes of laparoscopic floppy Nissen fundoplication (LNF) and laparoscopic Toupet fundoplication (LTF) for the treatment of gastroesophageal disease (GERD). Methods: A total of 84 patients with GERD were randomized to either LNF (n = 43) or LTF (n = 41) between January 2010 and January 2013. The primary endpoint measures were the DeMeester score, distal esophageal amplitude (DEA), peristaltic frequency, lower esophageal sphincter pressure (LESP), short-term and long-term postoperative dysphagia and recurrence rate. The secondary endpoints were improvements in symptom scores and quality of life (QoL), and perioperative complications. Results: LNF group had a lower DeMeester score and a higher LESP compared to LTF group after surgery (DeMeester score: P = 0.007; LESP: P = 0.027). The mean DEA and peristaltic frequency both improved significantly after surgery in 2 groups. There was no difference in the incidence of short-term adverse events (including dysphagia, heartburn, regurgitation et al.) between the two groups (P = 0.157). At the time of the latest follow-up, there was no difference in the incidence of symptomatic reflux symptom (heartburn and regurgitation) between the two groups (heartburn: P = 0.363; regurgitation: P = 1.000). A higher frequency of dysphagia was present in the LNF group compared with the LTF group (P = 0.023). Discussion: LNF is associated with an excessive elevation of LESP which may lead to further persistent dysphagia. Partial fundoplication may provide adequate reﬂux control, improve esophageal body motility and minimize complications associated with an 'over-tight' fundal wrap. Conclusion: LTF seems to be as safe and effective on the long-term as LNF, but with a lower incidence of postoperative dysphagia (ChiCTR-TRC-13003945). Highlights: Postoperative DeMeester score was lower in the LNF group. Postoperative LESP was higher in the LNF group. Postoperative DEA and peristaltic frequency improved significantly in the LTF group. Dysphagia was more common after LNF than after LTF. Postoperative reflux failed to show significant difference between 2 groups.